Performance Measurement Analysis of Ciawi Hospital During the Covid 19 Pandemic with A Balanced Scorecard Approach - Muhammad Irfan Ghifari; Amzul Rifin; Heny Kuswanti Suwarsinah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
RSUD Ciawi is a general hospital own by Bogor districts government and located at Main Road Puncak No, 479, Bogor Districts, West Java Province. RSUD Ciawi had fluctuation amount of revenue and problems managing budget to make RSUD Ciawi work more efficiently. Some problems are cause by marketing factor, the internal companies were not work optimally, and external factor that significantly effect RSUD Ciawi during Pandemic Covid 19. The purposes of this research are to identify the design of performance measurement system and measure the performance of RSUD Ciawi. Balanced scorecard measuring the performance with four perspectives that is financial perspective, customer perspective, internal business processes perspective and learning and growth perspective. The data were collected from November 2021 to March 2022 by interviewing top management of RSUD Ciawi, customers, and employees using questionnaires. RSUD Ciawi performance is in the category of very healthy (AAA) with a total score of 104.44 percent. RSUD Ciawi is expected to improve the inefficient administration system and poor human resource management. RSUD Ciawi is expected to be able to implement a performance measurement system with BSC. Through the application of the BSC concept, the Ciawi Hospital can assess its performance as a whole and more comprehensively either.